Learning Writing Explanatory Text Using Group Investigation Based on Learning Style (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Learning the writing skill of explanatory text demands the students to explain a certain phenomenon occurrence process. Therefore, it needs appropriate learning model to the learners’ learning style. The purpose of this research is to explain the effectiveness of learning writing explanatory text using group investigation based on eleventh graders’ of Senior High School learning style. This research with one group pre-test – post-test design used purposive sampling technique. The technique of data analysis of the instrument used validity and reliability test. Meanwhile, to test the sample used normality and homogeneity test. The final data analysis used a t-test to find out the comparison of the effectiveness of learning writing explanatory text based on learning style. The findings showed sensing typed learners gained 84.71 while intuition typed learners was 78.15. Learning writing explanatory using group investigation model was more effective for sensing typed learners. The significance of the research is to enrich research development on the educational field and to add more knowledge in learning writing explanatory text in educational institutions.